Ophiolites in the Central Asian Orogenic Belt record Cambrian subduction initiation processes - Mingshuai Zhu; Daniel Pastor–Galán; Matthijs A. Smit; Laicheng Miao; Miao Dong; Fuqin Zhang; Dorjgochoo Sanchir; Ariuntsetseg Ganbat; Chenghao Liu; Ye Luo; Shun Li (Communications Earth & Environment)
Abstract Subduction initiation remains elusive because no present example exists. Ophiolites formed over nascent subduction zones in the past provide the key to constraining the processes of subduction initiation. Here we document three Cambrian ophiolites with supra-subduction zone affinity, which likely reflect the inception of a plate-boundary scale subduction zone within the Paleo-Asian Ocean. Our findings, together with a compilation of Cambrian ophiolites in the Central Asian Orogenic Belt, indicate diachronous subduction initiation(s) along a > 6000 kilometer zone within the Paleo-Asian Ocean between 536 and 528 million years ago. The subduction initiation of the Paleo-Asian Ocean coincides with the closure of the Mirovoi Ocean following the collision of a series of microcontinents with the Siberian craton, likely representing a typical record of collision-induced subduction jump. Our observations and numerical modeling provide a new scenario that subduction initiations would locate at oceanic weak zones rather than passive margins of accreted microcontinents during collision-induced subduction process.